Penentuan Prioritas Utama Faktor Kecelakan Kerja dan Alternatif Pencegahannya Menggunakan Metode AHP - Sari Maribot Tinambunan; Irwan Budiman (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2023)
Occupational health and safety is a set of activities to prevent injuries and health problems for workers and to provide a safe and healthy workplace. PT PLN (Persero) ULP SIbolga Kota is a sub-unit under UP3 SIbolga that helps manage customer service and distribution electricity network service. Electrical distribution work is one of the jobs that have a high risk. Some of the injuries that often occur during the distribution of electricity are electric shock, burns, and falls from a height. The purpose of this study was to determine the main priority factors causing work accidents and alternative prevention using the Analytical Hierarchy Process (AHP) method. Data collection from expert respondents was carried out by distributing questionnaires. After analyzing the data, the consistency value (CR) of all risk criteria was determined to be less than 0.1, and this indicates that the decisions made by the experts are consistent. The main priority of the work accident factor at the criterion level is Discipline, with a weight of 0.372, the main priority of the work accident factor at the sub-criteria level is bad weather conditions, with a weight of 0.818, and the main priority of preventing work accidents in the alternative level is equipment maintenance with a weight of 0.298.